INTEGRATION OF FAMILY AND SCHOOL IN THE EDUCATIONAL PROCESS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
ANNOTATION This article analyzes the content, significance and modern forms of integration between family and school in the educational process. Cooperation between family and school is an important factor in the comprehensive development of the student's personality. The study covers methodological approaches to organizing the pedagogical process in close connection with the family, ways to improve the pedagogical literacy of parents and technologies that serve to increase the effectiveness of cooperation. It also substantiates the role of an integrated educational environment in the formation of social activity, moral values ​​and a sense of responsibility in students.ANNOTATSIYA Ushbu maqolada ta’lim-tarbiya jarayonida oila va maktab o‘rtasidagi integratsiyaning mazmuni, ahamiyati hamda zamonaviy shakllari tahlil qilinadi. O‘quvchi shaxsining har tomonlama rivojlanishida oila va maktabning o‘zaro hamkorligi muhim omil hisoblanadi. Tadqiqotda pedagogik jarayonni oila bilan uzviy bog‘liq holda tashkil etishning metodik yondashuvlari, ota-onalarning pedagogik savodxonligini oshirish yo‘llari va hamkorlikning samaradorligini oshirishga xizmat qiluvchi texnologiyalar yoritilgan. Shuningdek, integratsiyalashgan ta’lim-tarbiya muhitining o‘quvchilarda ijtimoiy faoliyat, axloqiy qadriyatlar va mas’uliyat hissini shakllantirishdagi o‘rni asoslab berilgan.АННОТАЦИЯ В статье анализируются содержание, значение и современные формы интеграции семьи и школы в образовательном процессе. Сотрудничество семьи и школы является важным фактором всестороннего развития личности ученика. В исследовании освещаются методические подходы к организации педагогического процесса в тесной связи с семьей, пути повышения педагогической грамотности родителей, технологии, способствующие повышению эффективности сотрудничества. Обоснована роль интегрированной образовательной среды в формировании у обучающихся социальной активности, нравственных ценностей, чувства ответственности.